Formulation of A Social Enterprise Model in Singapore - Wong, Yeow Hui (2010)
This management project takes us on an interesting journey into the Social Enterprise (SE) scene in Singapore by leveraging and using my nonprofit organization – Project: Senso Limited (aka SENSO) as a case study, as well as for future implementation.